Literature-Based Analysis of Lower Extremity Kinematics and Dynamics During Task-Oriented Physiotherapy for Rehabilitation Robot Design - Osiak, Tomasz; Osiak, Natalia; Falkowski, Piotr; Aktan, Mehmet Emin; Czerechowicz, Piotr; Omurlu, Vasfi Emre (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Robot-assisted rehabilitation is becoming an increasingly common method and allows using previously unavailable solutions. Designers of rehabilitation robots must ensure that their devices' exercises lead to the most functional movements. This review aimed to collect biomechanical, kinematic, and dynamic data on lower limb movement that can assist designers of rehabilitation robots. Seventeen studies were retrieved from Scopus and reviewed. The partial information regarding ranges of motion, angular velocities and joint torques during gait and daily life activities. It was found that the gait involves mainly motion in the parasagittal plane, while the activities of daily living often require full activation of the hip joint. The research proves that more experimental trials for modelling task-oriented rehabilitation movements are needed.
Keywords: additive manufacturing; Industry 4.0; process modelling; robotic welding; WAAM; Automation & Control Systems; Engineering; Instruments & Instrumentation; Robotics